INTERNALISASI NILAI PELESTARIAN DANAU TEMPE SOPPENG DALAM PEMBELAJARAN IPS - Hulipa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental degradation around Lake Tempe indicates a decline in ecological awareness among the younger generation. Social Studies (IPS) instruction in schools often focuses on mastering theoretical material and neglects the crisis facing the surrounding local ecosystem. This study aims to analyze strategies for internalizing the values of Lake Tempe conservation in Social Studies instruction and their impact on the development of students’ environmental awareness in Soppeng. Using a qualitative approach with a case study design, this research involved Social Studies teachers, students, and local community leaders. Data were collected through in-depth interviews, participatory observation of the learning process, and analysis of curriculum documents. The results indicate that the integration of Lake Tempe’s ecological values can be effectively implemented through three levels: the conceptualization of locally-oriented IPS material, the application of an eco-problem-based learning model, and concrete environmental conservation actions based on the school community. The internalization of these values successfully enhanced students’ contextual understanding of the interrelationship between the local community’s socioeconomic activities and the sustainability of the lake’s ecosystem. As a result, there was a transformation in students’ social attitudes and ecological behaviors, leading them to take greater responsibility for their surrounding environment. This study concludes that reinforcing local social studies content through eco-pedagogy is effective in bridging the gap between theoretical understanding of social studies and the reality of students’ environments.